The Effect of Competence, Price and Quality Of Service to The Satisfaction of Students - Moh. Saiful Bahri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
The number of factors that can affect satisfaction, researchers try to see from the aspects of competence possessed by lecturers, educational staff, prices or costs to be borne by students and service quality. This research was conducted in the Management Study Program of the Faculty of Economics, University of Panca Marga Probolinggo with a sample of 100 management students from a total number of management students of 1000. The purpose of this study was to determine whether there was a significant influence between competence, price and quality of service on student satisfaction. Based on the results of research analysis shows that competence, price and service quality together have a significant effect on student satisfaction, where the magnitude of F is 19,060 with a sig level of 0,000. Whereas the results of the research analysis partially showed that the coefficient t of the competency variable, -0.201, proved that competence had no partial effect on student satisfaction with a sig value of 0.841. The coefficient t of the price variable, 2.609, proves that prices affect student satisfaction. If the price is raised and followed by an increase in service it will increase student satisfaction. So partially the price has a significant effect on student satisfaction. The coefficient of service quality t arithmetic which is 5,531 with sig 0,000 means that partially the quality of service has a significant influence on student satisfaction, while the quality of service provides the greatest influence on student satisfaction.